Teacher educators’ nature of understanding of adult learning theories application in pre-service teachers’ classes - Matorevhu, Alois (Electronic Journal of Education, Social Economics and Technology, 2022)
Research publications show that they are many different theories which explain how adults learn, but none of them individually fully explains what happens when adults learn, hence cannot be applied universally. Each theory has its own merits and demerits, therefore to maximise learning, a combination of theories should be used. Adult teacher educators’ familiarity with this knowledge base of adult learning improves effectiveness in meeting adult learner needs, since implementation of the most effective ways for adult learning is made possible. The current study sought to find out the nature of experiences of secondary school teachers recruited to be teacher educators at a secondary teachers’ college, had during the transition from teaching children (pedagogy) to teaching adults (pre-service mathematics and science teachers). Interviews were done, with the view to enable teacher educators to compare their experiences during training (as adult learners) in various teacher education institutions, teaching children at secondary school level, and teaching adults at the teachers’ college in the current study. Interview responses were coded to come up with themes which were analysed. Findings show that learning and application of adult learning theories is a missing link in teacher preparation institutions in Zimbabwe. In order to align teacher preparation with the current Zimbabwean curriculum, training institutions must prepare prospective teachers for both pedagogy and adult learning theories, so that they adapt as the situation requires. This resonates with metagogy, a hybrid of pedagogy and adult learning theories. Preparing teachers this way is in line with best practices, which engender competitiveness to deal with diverse teaching and learning situations, in the 21st century.